Strategi Promosi Dalam Menciptakan Brand Awareness Produk Kuliner - Pande Made Sri Suwar Septiani (Universitas Pendidikan Nasional, 2015)
The development of tourism sector in Bali, especially in Ubud provides manyopportunities for entrepreneurs to start innovating in various fields of business, especiallybusinesses in culinary, because it can not be denied is now the tourists who come to Bali notjust come to enjoy the beauty of the culture and nature of the island of Bali yet tourists arealso looking for a culinary hallmark of the region. Increasing number of same type ofbusiness, especially in the culinary field, the more creative entrepreneurs in the process ofpromotion, a wide variety of promotional strategies used to promote their business names,products they sell as well as the advantages offered from the other competitors.Of course, to draw up appropriate strategies to improve customer satisfaction andloyalty at a culinary entrepreneurs must consider a lot of things that will be able to create apositive brandawaress the name of his business. And issues raised in this research is how theimplementation of promotional strategies carried out in creating brand awareness ofcustomers towards culinary products in Bebek Tepi Sawah, Ubud, Gianyar.Keywords: Promotion Strategy, Brand Awareness, Culinary Products